SALURAN PEMASARAN SAYUR SAWI PACKCOY (Brassica rapa subsp. chinensis) DENGAN SISTEM HIDROPONIK WICK - Rudy Wicaknono; Yuhanin Zamrodah; Jeka Widiatmanta (Jurnal Ilmiah Hijau Cendekia, 2021)
Farmers' incomes are strongly influenced by the marketing of their products and the prevailing prices, where marketing that is less efficient is the small part that farmers receive from the price paid by the final consumer. The purpose of this study was to determine the marketing channel of Packcoy Mustard (Brassica rapa subsp. chinensis) with the Wick Hydroponic System. This type of research is descriptive quantitative research. The research was conducted in the Regency and City of Kediri, East Java, with 20 hydroponic farmers as respondents. The method of data collection carried out in this study used documentation, interviews and documentation. Method of data analysis with descriptive analysis. The marketing channels run by Guyup Rukun Hydroponics include channel patterns I, II and III so that it is hoped that people's purchasing power will increase and the production scale will be wider.